Keeping our fingers crossed on 2nd generation EGFR TKIs: is better good enough? - Ou, Sai-Hong Ignatius (Translational Lung Cancer Research; Vol 2, No 1 (February 14, 2013): Translational Lung Cancer Research, 2012)
It has been almost a decade since the first generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) has been approved for use in non-small cell lung cancer (NSCLC). When EGFR TKIs (gefitinib, erlotinib) were approved, it was based on response rates (gefitinib) or significant improvement in overall survival when compared to placebo (erlotinib) in 2nd line or 3rd line treatment in an unselected NSCLC patient population regardless of histology, gender, or smoking status (1,2).